Evaluation of a novel monoclonal enzyme immunoassay for detection of Helicobacter pylori antigen in stool from children. Issue 6 (1st June 2003) - Koletzko, S; Konstantopoulos, N; Bosman, D; Feydt-Schmidt, A; van der Ende, A; Kalach, N; Raymond, J; Rüssmann, H
Abstract : Background: Reliable non-invasive methods for detection of Helicobacter pylori infection are required to investigate the incidence, transmission, and clearance of infection in childhood. Aim: To evaluate a new monoclonal enzyme immunoassay (EIA) (FemtoLab H pylori Cnx) for detection of H pylori antigen in stool in a large cohort of children compared with invasive diagnostic methods and the 13 C urea breath test. Patients and methods: A total of 302 symptomatic previously untreated children (aged 0.5–18.7 years; 148 girls) were recruited at three centres. H pylori status was defined by results of culture, histology, the rapid urease test, and the 13 C urea breath test. Stool samples were investigated locally by the EIA using two different production lots. According to the manufacturer's recommendations, an optical density (OD) of 0.150 was used as a cut off value. Results: OD values clearly differentiated between the 92 H pylori infected and the 210 non-infected children (median (5th–95th percentiles) 2.729 (0.232–>4.000) v 0.021 (0.009–0.075)). Only two false positive and two false negative results occurred, giving a sensitivity, specificity, positive predictive value, and negative predictive value of 98%, 99%, 98%, and 99%, respectively. No significant relation was found between age and OD values in infected or non-infected children. Conclusions: The monoclonal stool antigen EIA was excellent in diagnosing H pylori infection in symptomatic children. Accuracy was independent of the laboratory, production lot used, or the child's age. Because only 18/116 children <6 years of age were infected with H pylori, further validation of the test is needed in young infected children.